Vision-based Hand Recognition Based on ToF Depth Camera. Issue 1 (2nd January 2018) - Yu, Chao-Wei; Liu, Chin-Hsuan; Chen, Yen-Lin; Lee, Posen; Tian, Meng-Syue
Abstract: The current gesture recognition methods mostly adopt the classification-based approaches such as Neural Network (NN), Support Vector Machine (SVM), Hidden Markov Model (HMM) etc. As for the input image features, most research studies combined the color and depth images (ex. RGB-D) to obtain more accurate information of hand area, and such techniques may cost high computational resources and energy consumptions. To provide a low-cost gesture recognition method for wearable devices, this thesis used merely the Time-of-Flight depth camera to achieve a lightweight gesture recognition method. In most traditional gesture recognition methods, users have to wear gloves or bracelets to let depth cameras being able to accurately capture hands areas, and so that the hand contours, palm's distances, and angle feature can be obtained. Moreover, the Earth Mover's Distance (EMD) algorithm, which is adopted in most gesture recognition approaches, costs high computational times. In this study, to avoid wearing gloves or bracelets, we propose a new algorithm that can compute the wrist cutting edges and capture the palm areas. In addition, this thesis proposes an efficient finger detection algorithm to judge the number of fingers, and significantly reduce the computing times. In the experimental results, our proposed method achieves a recognition rate of 90% and the performance has 5 frames per second on NVIDIA TX1 embedded platforms. Abstract :